Tronc : valuing the future of newspapers - Rosenthal, Jean W., 1945- (SAGE Knowledge. Cases., 2018)
May 2016, the Tribune Publishing board rejected a second all-cash buyout offer from Gannett Publishing, $15/share, up from an initial unsolicited bid of $12.25. The debate became public and heated, as Gannett made an appeal directly to the Tribune's non-management shareholders. The negotiations ultimately failed, but the underlying questions remained. Should the Board have accepted Tribune's offer? What was the right price? What is the best way to value a company like tronc? What might other players do next?